Early Experience of the Single-Port Robotic Transvesical Radical Prostatectomy: Case Series - Jae Hoon Chung; Hwanik Kim; Woo Jin Bang; Cheol Young Oh; Jin Seon Cho (Journal of Urologic Oncology)
Purpose This study evaluated the feasibility and safety of single-port transvesical robotic radical prostatectomy. Materials and Methods Four patients underwent a transvesical robotic radical prostatectomy using a singleport robotic system. The procedure involved a 2.5-cm suprapubic incision to access the anterior bladder wall, which was incised by approximately 2 cm. Utilizing a floating-docking technique. Results All surgeries were successfully completed without the need for additional ports or open conversion. Intraoperative complications were not observed. The median (interquartile range, IQR) console time was 159 (96–198) minutes. The median (IQR) estimated blood loss was 350 (300–700) mL. The median (IQR) duration for Foley catheter removal and patient discharge postsurgery was 7.5 (6–10) days. None of the patients experienced total incontinence after Foley catheter removal, and at 1-month postsurgery, all patients used only a safety pad. Pathology revealed positive surgical margins in 2 patients (both with pT3a and pT3b), with one of these patients having a persistent prostate-specific antigen level of 0.48 ng/mL at 1-month postsurgery. Additionally, 2 patients experienced gross hematuria within 2-week postdischarge. Conclusion This series demonstrates that single-port robotic transvesical radical prostatectomy is a feasible procedure with favorable perioperative functional outcomes. This offers the advantage of rapid continence recovery without oncological disadvantages.